1991
DOI: 10.1002/j.1460-2075.1991.tb07665.x
|View full text |Cite
|
Sign up to set email alerts
|

vHNF1 is a homeoprotein that activates transcription and forms heterodimers with HNF1.

Abstract: vHNF1 and HNF1 are two nuclear proteins that bind to an essential element in the promoter proximal sequences of albumin and of many other liver‐specific genes. HNF1 predominates in hepatocytes but is absent in dedifferentiated hepatoma cells. These cells contain vHNF1 but fail to express most of the liver traits. In the present work we have isolated cDNA clones for vHNF1 and found that it is a homeoprotein homologous to HNF1 in regions important for DNA binding. Unexpectedly, vHNF1 transactivated the albumin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
219
1
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(231 citation statements)
references
References 44 publications
(60 reference statements)
9
219
1
2
Order By: Relevance
“…HNF-1beta is a transcription activator that regulates the promoters or enhancers of genes that are expressed in a liver-specific manner, such as albumin and alpha-fetoprotein. [16][17][18] In normal tissue, HNF-1beta is expressed not only in the liver, but also in the digestive tract, pancreas, and kidney, where it plays a role as a major regulator of glucose homeostasis. 19 It has been shown that the reduction of HNF-1beta expression by RNA interference induced apoptosis in ovarian clear cell carcinoma cell lines, suggesting that HNF-1beta expression is essential for the survival of clear cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…HNF-1beta is a transcription activator that regulates the promoters or enhancers of genes that are expressed in a liver-specific manner, such as albumin and alpha-fetoprotein. [16][17][18] In normal tissue, HNF-1beta is expressed not only in the liver, but also in the digestive tract, pancreas, and kidney, where it plays a role as a major regulator of glucose homeostasis. 19 It has been shown that the reduction of HNF-1beta expression by RNA interference induced apoptosis in ovarian clear cell carcinoma cell lines, suggesting that HNF-1beta expression is essential for the survival of clear cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…HNF1 and HNF1, two members of the HNF1 transcription factor family, share amino-terminal dimerization domain and POU-like DNA-binding homeo domain, but not carboxyl-terminal transcriptional activation domain, and they bind DNA as homodimers or heterodimers [24,34,35]. Our data demonstrated that in the human Cbg proximal promoter, HNF1 or HNF1 had different effect on the basal promoter activity.…”
Section: Discussionmentioning
confidence: 69%
“…TCF1 and TCF2, respectively, encode the transcription factors hepatocyte nuclear factor 1a and b (HNF1a and HNF1b), two POU-homeodomain proteins that bind to an essential element in the proximal promoter sequences of albumin and many other tissue-specific genes and are associated with development, metabolism and cancer (Cereghini et al, 1987;Courtois et al, 1987;Frain et al, 1989;Rey-Campos et al, 1991). For instance, TCF2 defects cause developmental abnormalities in multiple tissues, including kidney and pancreas (Horikawa et al, 1997;Haumaitre et al, 2005), and Bluteau et al (2002) identified biallelic mutations of TCF1 in hepatic adenomas (Bluteau et al, 2002).…”
mentioning
confidence: 99%